2018
DOI: 10.3390/s18124254
|View full text |Cite
|
Sign up to set email alerts
|

An Eight-Direction Scanning Detection Algorithm for the Mapping Robot Pathfinding in Unknown Indoor Environment

Abstract: Aiming at the problem of how to enable the mobile robot to navigate and traverse efficiently and safely in the unknown indoor environment and map the environment, an eight-direction scanning detection (eDSD) algorithm is proposed as a new pathfinding algorithm. Firstly, we use a laser-based SLAM (Simultaneous Localization and Mapping) algorithm to perform simultaneous localization and mapping to acquire the environment information around the robot. Then, according to the proposed algorithm, the 8 certain areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Article [ 34 ] illustrates the applicability of the method through experiments with an unmanned ground vehicle in both structured and unstructured environments. The methodologies for defining movement routes for robots are also presented in works [ 35 , 36 , 37 , 38 ]. In this respect, the results of experiments that show non-standard solutions are particularly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Article [ 34 ] illustrates the applicability of the method through experiments with an unmanned ground vehicle in both structured and unstructured environments. The methodologies for defining movement routes for robots are also presented in works [ 35 , 36 , 37 , 38 ]. In this respect, the results of experiments that show non-standard solutions are particularly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Robust pose estimation and environment mapping are of great significance in the execution of robotic tasks, such as motion control and navigation. The robot’s pose and the scene’s map can be obtained by utilizing robotic sensors, such as wheel encoders, inertial measurement units [2,3,4], lasers [5,6], and cameras [7,8,9]. Among these solutions, the visual-based method is one of the more effective approaches because cameras can conveniently capture informative images to estimate the robot’s poses and perceive its surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…According to its algorithmic principle, the visual SLAM system can be divided into the direct formulation and the indirect formulation [4]. Compared with the indirect visual SLAM, the direct formulation can establish dense, semi-dense, sparse 3D reconstructions that are valuable for the navigation of ground mobile equipment [5]. In addition, research has shown that the mapping performance of the direct approach was more robust than the indirect one for the low-texture-features environment [6].…”
Section: Introductionmentioning
confidence: 99%